2013
DOI: 10.1007/978-3-642-39354-9_19
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Visual Attention and Workload by Experts and Novices in the Cockpit

Abstract: Abstract. Under high pressure of flight mission and dynamic aircraft maneuvers in the tactic missions, pilot faces additional difficulties and increased mental workload. Workload could increase the error of flight operation, decrease efficiency of pilot's decision-making. Experts had significantly shorter dwells, more total fixations, more aim point and airspeed fixations and fewer altimeter fixations than novices, experts were also found to have better defined eyescanning patterns. This research applies the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…A frequently employed factor when examining visual attention is the level of expertise; not only in cartography but in many other domains (e.g., [24][25][26][27]). The focus on this factor is grounded in the novice-expert paradigm which assumes a different approach by an expert and a novice in solving tasks, and also independent variables influencing it [28,29].…”
Section: Searching For Group Differences Among Map Usersmentioning
confidence: 99%
“…A frequently employed factor when examining visual attention is the level of expertise; not only in cartography but in many other domains (e.g., [24][25][26][27]). The focus on this factor is grounded in the novice-expert paradigm which assumes a different approach by an expert and a novice in solving tasks, and also independent variables influencing it [28,29].…”
Section: Searching For Group Differences Among Map Usersmentioning
confidence: 99%
“…For example, a study of middle school students who had a diagnosis of attention deficit hyperactivity disorder (ADHD) demonstrated that the students had a wide range of significant improvements in cognitive functions such as short and long-term memory, ability to focus, and significant improvements in behaviors, both at home and in school ( Lloyd et al, 2010 ). A study of 41 fighter pilots engaging in flight simulator tasks found a significant correlation between higher levels of performance and heart rhythm coherence as well as lower levels of frustration ( Li et al, 2013 ).…”
Section: Psychophysiological Coherence and Well-beingmentioning
confidence: 99%
“…In a study of the effects of five different types of prayer on HRV, it was found that all types of prayer elicited increased cardiac coherence; however, prayers of gratefulness and prayers that focused on heart felt love resulted in definitively higher coherence levels ( Stanley, 2009 ). There are also many studies showing that the practice of breathing at 6 breaths per minute, supported by HRV biofeedback, induces the coherence rhythm and has a wide range of benefits ( Lehrer et al, 2003 , 2006 ; Siepmann et al, 2008 ; Hallman et al, 2011 ; Henriques et al, 2011 ; Ratanasiripong et al, 2012 ; Beckham et al, 2013 ; Li et al, 2013 ). It has also been shown that tensing the large muscles in the legs in a rhythmical manner at a 10 seconds rhythm can induce a coherent heart rhythm ( Lehrer et al, 2009 ).…”
Section: Self-regulation Techniques That Increase Cardiac Coherencementioning
confidence: 99%
“…See also the comprehensive review of pilot scanning studies by Ziv (2017). As an example, a vast majority of studies revealed that experienced pilots exhibited shorter dwell times on the instrument displays but checked them more frequently (Bellenkes, Wickens, & Kramer, 1997;Kasarskis, Stehwien, Hickox, Aretz, & Wickens, 2001;Kramer, Tham, Konrad, Wickens, & Lintern, 1994;Li, Chiu, Kuo, & Wu, 2013;Sullivan, Yang, Day, & Kennedy, 2011;Tole, Stephens, Vivaudou, Ephrath, & Young, 1983). These finding suggest that expertise is associated with more efficient visual scanning, that is, greater skill at extracting relevant information in a shorter amount of time.…”
Section: Situation Awarenessmentioning
confidence: 99%